Realisasi Bantuan Rehabilitasi Jaringan Irigasi Tersier kepada Subak (Kasus Program UPSUS PAJALE di Subak Margasengkala, Desa Bedulu, Kecamatan Blahbatuh, Kabupaten Gianyar) - KESUMA, I MADE WIRA ADI; SUARDI, I DEWA PUTU OKA; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.3, Juli 2017, 2017)
Realization of the Tertiary Irrigation Rehabilitation Aid To Subak (A Case of UPSUS PAJALE Program at Subak Margasengkala of Bedulu Village, Blahbatuh Sub-District, Gianyar Regency) Rehabilitation of the tertiary irrigation network is one of the assistance of the special effort program (UPSUS) to increase the rice-paddy, corn and soybean productions (PAJALE) in realizing food self-sufficiency for three years from 2015-2017. The study aims to determine the conditions of irrigation networks before and after obtaining aid, aid proposal procedures, and suitability between proposals of assistance with those received by Subak. The research was conducted in Subak Margasengkala, Bedulu Village, Blahbatuh Sub-District, Gianyar. The selection of the research location was done by purposive sampling. Respondents in the study were 37 people, consisting of 34 farmers, a chief of irrigation system of pekaseh, an agricultural extension agent, and a respondent of the Gianyar Regency Agriculture Office.The results showed that the condition of Subak Margasengkala irrigation network was damaged along 200 m. Procedures for obtaining the aid is by submission of requests for aid to the department of agriculture in the form of a proposal. The realization of the rehabilitation of tertiary irrigation networks in Subak Margasengkala was not in accordance with what had been proposed, the proposed irrigation network to be rehabilitated was along 200 m, with the required funding of Rp.103,000,000, but in its realization it was only for 116 m with funds received of 23 million Rupiahs.Based on the findings of the study, it is suggested to the government to continue to provide assistance until the Subak or irrigation organization is able to independently overcome the problem of irrigation network damage. In addition, the farmers should be willing and able to work together in self-help in order to independently overcome the problem of damage to the irrigation network.